Terapi Kombinasi Air Perasan Daging Buah Mengkudu (Morinda citrifolia L.) dan Mentimun (Cucumis sativus L.) untuk Menurunkan Tekanan Darah pada Pasien Hipertensi - Novia Anggraini; Wisnu Cahyo Prabowo; Hadi Kuncoro (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Noni (Morinda citrifolia L.) and cucumber (Cucumis sativus L.) fruit are plants that have antihypertensive activity. The active ingredient scopoletin, anthosianin, xeronin in noni and high potassium in cucumber can lower blood pressure. This study aims to determine the characteristic description, hedonic quality test and the effect of giving a combination noni and cucumber squeezed water flesh of fruit on reduction in the systolic and diastolic blood pressure of hypertension patients in Muara Jawa District, East Kalimantan. The research method used was quasi experimental and research procedures measuring pre and post test being given treatment for 7 days. The highest percentage of respondents collected data obtained are aged 36-45 years as much as 45%, women70%, junior high school education 45%, family history 60%, frequent exercise habits 55% and normal BMI 45%. The highest percentage of sample hedonic quality test collected data obtained are the flavor test was sweet by 65%, the aroma test was sharp by 75% and the texture test was soft by 75%. The results of statistical tests using the paired sample t-test method showed a significant decrease in systolic blood pressure p = 0.000 < ? (0.05) of 12.3 mmHg and diastolic blood pressure p = 0.000 < ? (0.05) of 5.4 mmHg. Based on the results of the study, it can be concluded that giving a combination noni and cucumber squeezed water flesh of fruit can have reduced effect on systolic and diastolic blood pressure of hypertension patients.